The association between recreational physical activity and depression in the short sleep population: a cross-sectional study - You, Yanwei; Wei, Mengxian; Chen, Yuquan; Fu, Yingyao; Ablitip, Alimjan; Liu, Jianxiu; Ma, Xindong (Frontiers in Neuroscience, 2023)
Background Short sleep is more common in the modern society. Recreational physical activity (RPA) like exercise brings both mental and physiological benefits to depression; paradoxically, lack of sleep is harmful. Evidence on the association between RPA and depression in the short sleep population is limited. Methods Participants with short sleep condition from the National health and Nutrition Examination Surveys (NHANES 2007–2018) were included in the present study. Short sleep condition was defined as ≤ 7 h per night. Sleep duration and RPA status were self-reported in NHANES by the Physical Activity Questionnaire using a 7-day recall method. Multivariable logistic regression was applied to evaluate the association between RPA and depression. Additionally, the non-linear relationship between RPA and depression was evaluated using the threshold effect analysis and restricted cubic spline. Results This cross-sectional study comprised 6,846 adults' data, and the weighted participants were 52,501,159. The weighted prevalence of depression was higher in females, which took up 65.85% of all depression patients. In fully adjusted models, sufficient volume of RPA was associated with lower depression risks, with OR (95% CI) =0.678 (0.520, 0.883). Further analysis revealed a U-shaped association between RPA and incident depression, and the inflection point was 640 MET-minutes/week. When RPA <640 MET-minutes/week, increased RPA was associated with lower risk of incident depression, with OR (95% CI) = 0.891 (0.834, 0.953). When RPA ≥ 640 MET-minutes/week, the benefits of RPA seemed to be not significant, with OR (95% CI) = 0.999 (0.990, 1.009). Conclusion Our findings observed associations between RPA condition and incident depression in the short sleep population. Moderate RPA was beneficial to maintain mental health and associated with lower incidence of depression for short sleepers, but excessive RPA might increase the risk of depression. For general short sleepers, keeping the RPA volume approximately 640 MET-minutes/week was beneficial to lower risks of depression. Gender difference should be considered as an important factor for further studies to examine these relationships and explore mechanisms.